Strategies to increase cellulase production with submerged fermentation using fungi isolated from the Brazilian biome - Genilton da Silva Faheina Junior; Mariza Vieira da Fonseca Sabóia Amorim; Caroline Gondim de Souza; Diego Menezes de Sousa; Kally Alves de Sousa; Gustavo Adolfo Saavedra Pinto (Acta Scientiarum. Biological Sciences, 2015)
Studies on new microbial sources of cellulase and accurate assessment of the steps that increase cellulase production are essential strategies to reduce costs of various processes using such enzymes. This study aimed at the selection of cellulase-producing filamentous fungi, and at the research of parameters involving cellulase production by submerged fermentation. The first test consisted of selecting the best cellulase-producing microorganisms (FPase) in Erlenmeyer flasks containing 200 mL of specific growth medium. The next test was designed to further investigate the enzyme production in fermentation with four types of soluble sugars: glucose, lactose, sucrose and xylose. In bioreactor tests, three different inoculation strategies were analyzed. The best FPase activity was presented by the strain Trichoderma sp. CMIAT 041 (49.9 FPU L-1) and CMCase by the fungus Lasiodiplodia theobromae CMIAT 096 (350.0 U L-1). Sucrose proved to be the best option among the soluble sugars tested, with higher rates of FPase activity (49.9 FPU L-1) and CMCase (119.7 U L-1). The best inoculation strategy for the bioreactor was a spore suspension obtained from a semi-solid state fermentation of wheat bran for 72h.